A MULHER TRANSGRESSORA: GÊNERO, CRIMINALIDADE E O TRÁFICO INTERNACIONAL DE DROGAS NO CONTEXTO PRISIONAL EM TIRES, PORTUGAL - Lindoso Sarges, Glaucia (Universidad de Panamá. Centro de Investigaciones de la Facultad de Humanidades, 2021)
With the pandemic scenario, criminal organizations have changed the modus operandi of the so-called drug route. However, the criminal landscape in Portugal has undergone many changes, before the latest world events, one of which has been the dizzying increase in foreign women in criminal practices, especially those involving international drug trafficking. Among these, the South American ones stand out, specifically the Brazilian ones. The reasons for such an increase lead us to numerous reflections, from an analysis of the critical theory of female crime to the use of an approach that contributes to “giving voice” to transgressive women. Furthermore, the background of international drug trafficking in Europe is related to a specific plot, circumscribed, above all, to the situation in Portugal, which, unlike other countries, has served as a gateway for the entrance of the so-called “drug couriers”.